Quantitative pivot shift assessment using combined inertial and magnetic sensing - Labbé, David R.; Li, Di; Grimard, Guy; de Guise, Jacques A.; Hagemeister, Nicola (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2015)
Purpose The purpose of the study was to demonstrate the feasibility of a new measurement system using micro-electromechanical systems (MEMS)-based sensors for quantifying the pivot shift phenomenon. Methods The pivot shift test was performed on 13 consecutive anterior cruciate ligament-deficient subjects by an experienced examiner while femur and tibia kinematics were recorded using two inertial sensors each composed of an accelerometer, gyroscope and magnetometer. The gravitational component of the acquired data was removed using a novel method for estimating sensor orientations. Correlation between the clinical pivot shift grade and acceleration and velocity parameters was measured using Spearman’s rank correlation coefficients. Results The pivot shift phenomenon was best characterized as a drop in femoral acceleration observed at the time of reduction. The correlation between the femoral acceleration drop and the clinical grade was shown to be very strong ( r = 0.84, p < 0.0001). Conclusions The present study demonstrates the feasibility of quantifying the pivot shift using MEMS-based sensors and removing the gravitational component of acceleration using an estimation of sensor orientation for improved correlation to the clinical grade.